2016
DOI: 10.1111/imre.12185
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Composition and School Performance in the Secondary Education of Turkish Migrant Students in Seven Countries and 19 European Educational Systems

Abstract: This article examines the effect of the ethnic composition on school performances in secondary education for Turkish students, using both cross-national and Swiss national PISA 2009 data. At the school level our results show no effect of the proportion of natives or the proportion of coethnics and a negative association between ethnic diversity (we employ a residualized score of diversity on the proportion of migrants) and math performances. Consequently, we find no evidence for social capital advantages and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Finally, given the importance of identity development for psychological wellbeing, our paper provides a partial corrective to accounts of classroom ethnic diversity that have highlighted the negative consequences for pupils' outcomes (e.g. Veerman and Dronkers 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given the importance of identity development for psychological wellbeing, our paper provides a partial corrective to accounts of classroom ethnic diversity that have highlighted the negative consequences for pupils' outcomes (e.g. Veerman and Dronkers 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting positive diversity climate is of utmost importance in diverse schools: According to a study by Rjosk et al ( 2017 ), a high proportion of ethnic minority students or ethnically diverse classrooms are connected with students' lower sense of belonging as well as lower educational outcomes of individual students. Other studies have shown no effect of the proportion of natives or co-ethnics at the school on school performances in secondary education for Turkish origin students, and a negative association between ethnic diversity and learning outcomes in math, possibly because of lesser opportunities to gain access to social networks of native peers (Veermlan and Dronkers, 2016 ). However, also contradictory results exist: In the Netherlands, Peetsma et al ( 2006 ) found that a greater amount of migrants in a class was positively associated with math scores for students from Turkish and Moroccan origin, and they explain this result with the expertise that teachers have gained in adapting their teaching according to students' needs (see also Veermlan and Dronkers, 2016 ).…”
Section: Previous Research and Contextmentioning
confidence: 98%
“…In the 1970s, refugees (mainly Kurdish, Assyrian, or Syriani) started to flee from Turkey to Western Europe (Schnell, 2014 ). At the moment, people with Turkish origins are the largest immigration group in Europe (Veermlan and Dronkers, 2016 ).…”
Section: Previous Research and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…These seemingly contradictory results could partly be explained by the different macro-contexts of each study. Cross-country studies have shown that segregation and ethnic diversity have opposite relationships with school performance (Veerman & Dronkers, 2013), ethnic tolerance (Janmaat, 2012) and classroom disruption (Veerman, 2015) in different countries. In countries with a more inclusive immigration policy, segregation can have less of an impact, or even show no negative influence.…”
Section: Contextual Characteristics and Country Differencesmentioning
confidence: 99%